The dynamics of vocal onset. (March 2019) - Lebacq, J.; DeJonckere, P.H.
Highlights: Vocal onset is defined as the process occurring between the first detectable oscillatory glottal movement and the steady-state vocal fold vibration. High speed imaging, photoglottography, flowglottography, EGG and ultrasonoglottography are suitable for identifying and analyzing hard, soft and breathy onsets. Flow- and photoglottography are the most sensitive for detecting the first glottal movements in soft and breathy onsets. The onset phase may comprise up to 30 cycles, depending to some extent on vocal fold adduction speed and expiratory flow. From the first onset cycles on, the intraglottal pressure during the opening phase of the glottis exceeds that during the closing phase. Abstract: Vocal onset is the process occurring between the first detectable oscillatory glottal movement and the steady state vibration of the vocal folds. To some extent, the voice onset mirrors the voice offset. High speed imaging, photo-, electro-, flow- and ultrasonoglottography and sound analysis have been used in combinations to allow detailed qualitative insight into the phenomenon. Moreover, the instantaneous intraglottal pressure can be computed from the combined records of transglottal airflow and glottal area. A large number of vocal onsets of different types were analysed in various conditions of modal healthy phonation. Vocal folds (VF) vibration can start either from a closed glottis (hard onset) or from an open glottis (soft/breathy onset). In a soft onset, the amplitude of oscillations progressively increases over 2 to more than 30 cycles, before the first clear closed plateau is achieved. It is not possible to define whether the first movement of VF is towards medial or lateral. Hard, soft and breathy onsets can be clearly identified. Flow- and photoglottography are the most sensitive signals in detecting the first glottal movements in soft and breathy onsets. The shape of the EGG signal depends on the contact of the VF edges. The duration of the onset phase is to some extent related to VF adduction speed and peak expiratory flow. The ultrasound technique is sensitive, but lacks physiological interpretation. From the first onset-cycles on, the intraglottal pressure during the opening phase of the glottis exceeds that during the closing phase. During soft/breathy onsets with a sufficiently large number of cycles, when the vibrating mass increases, a trend appears toward a slight progressive decrease of the fundamental frequency of the oscillations, likely related to the increasing vibrating mass.